Engagement of patients with scleroderma to revise an internet self-management program - Janet Poole; Sharon Newbill; Jennifer Serrano; Dana Rosson; Josephine Battyany; Laura Dyas; Luke Evnin; Dennis Raisch; Cynthia Maxwell; Mary Alore; Saville Kellner; Pedro Cuencas; et al. (The Beryl Institute, 2019)
Systemic sclerosis (SSc) or scleroderma is a rare connective tissue disease. Many people do not have access to education programs. A self-management program was developed several years ago based on the literature and input from people with SSc. However, new therapies and treatment options have been developed since the program was developed. The purpose of this qualitative study was to identify and remedy gaps in an internet SSc self-management program to improve the quality of critical information relevant to effective management of the disease. Six focus groups with 30 participants with SSc were conducted: 2 telephone groups and 4 face-to-face groups. Prior to the focus group meetings, participants reviewed the existing website. A semi-structured interview guide elicited participants' responses. Gaps were expressed in affect and positive affirmation; disease and symptom management; self-advocacy; information for caregivers, families, coworkers and strangers; tracking systems; information about local support groups; pictures and information on underrepresented groups; and general format. Discussants were positive regarding the audio voice over, exercise module, current content, health logs and checklists. People with SSc identified additional content to improve the internet self-management program. Many of the suggestions were incorporated into the existing program as modifications and additions to existing modules, patient testimonials, worksheets, resources sheets, and/or links to additional websites. People with rare, chronic conditions such as SSc need education and reliable sources of information and self-management skills. Experience Framework This article is associated with the Innovation & Technology lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Innovation%20%26%20Technology%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens